Finite element modelling for electric field distribution around positive streamers in oil - Nguyen, Dung Van; Chuong, Le Vinh (Vietnam Journal of Science and Technology, 2020)
Electric field distribution of positive streamers during propagation was determined with the finite element method by using COMSOL multiphysics. Modelling was performed at 210 kV and 270 kV. The geometrical shape of streamers was modelled with cylinder and sphere for the case of 210 kV while a growing cylinder was used for streamer propagation at 270 kV. In addition, a spherical model was used for determining the correlation between streamer branching and the electric field. It is obtained from the simulation results that the 2nd mode streamers has the electric field at channel tips of about 0.1 MV/cm while 8.3 MV/cm was received for the 4th mode streamers. The simulation results also reveal that the shielding effect resulting from streamer branching significantly reduces the electric field at the channel tips, and the shielding effect disappears with the angle a between channels is about 30o-60o depending on the size of streamer envelope. The hypothesis on correlation among velocity, streamer branching and electric field is suggested